2012
DOI: 10.1038/jhg.2012.55
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of prostaglandin E2 receptor subtype EP4 gene in aspirin-intolerant chronic urticaria

Abstract: Prostaglandin E2 receptor subtype EP4 (PTGER4) is one of the four subtypes of receptors for prostaglandin E2 (PGE2). Overproduction of cysteinyl leukotriene in mast cells may be related with suppression of PGE2 in patients with aspirin hypersensitivity. Considering the association of PTGER4 in mast cells, urticaria-and aspirin-related disease, we hypothesized the genetic variability of PTGER4 may be associated with aspirin-intolerant chronic urticaria (AICU). The case-control study was performed in 141 with AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The ALOX5 gene encodes a member of the lipoxygenase gene family and plays a dual role in the synthesis of leukotrienes from arachidonic acid. By comparison, the case-control studies performed on NAR to aspirin showed an association with three other genes of the arachidonic acid pathway, LTC4S, TBXA2R, and PTGER4, and only one, ALOX5, which was also associated with NAR to NSAIDs (33,39,41,42). This is consistent with the fact that aspirin and NSAIDs inhibit distinct enzymes of this pathway.…”
Section: à3supporting
confidence: 70%
See 3 more Smart Citations
“…The ALOX5 gene encodes a member of the lipoxygenase gene family and plays a dual role in the synthesis of leukotrienes from arachidonic acid. By comparison, the case-control studies performed on NAR to aspirin showed an association with three other genes of the arachidonic acid pathway, LTC4S, TBXA2R, and PTGER4, and only one, ALOX5, which was also associated with NAR to NSAIDs (33,39,41,42). This is consistent with the fact that aspirin and NSAIDs inhibit distinct enzymes of this pathway.…”
Section: à3supporting
confidence: 70%
“…1). Among the 42 selected studies that reported genetic predictors in association with immediate-type hypersensitivity, 19 were related to BLs (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) (Table 1), 12 to aspirin (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) (Table 2), and eight to other NSAIDs (43-50) (Table 3). Three studies reported genetic predictors in association with biologicals, including hypersensitivity to asparaginase (51), EGF receptor inhibitors (52), and infliximab (53) ( Table 4).…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported associations for 2 SNPs in PGE1R (rs3810253 and rs3810255) and 1 in PGER2 (rs1254598) [88] in NIUA, neither of which was found in Asian NERD patients [94]. The MAF of PTGER4 -1254G>A was recently found to be higher in NECD patients than in healthy individuals [96]. Finally, the rs8004654 polymorphism in PGDR was shown to be significantly associated with NIUA in 2 independent Spanish populations [88], as well as in American asthmatics [97].…”
Section: Enzyme and Receptor Genes From The Arachidonic Acid Metabolimentioning
confidence: 99%